2021
DOI: 10.3389/fphar.2021.768700
|View full text |Cite
|
Sign up to set email alerts
|

Farrerol Ameliorated Cisplatin-Induced Chronic Kidney Disease Through Mitophagy Induction via Nrf2/PINK1 Pathway

Abstract: Previously, Our study has showed that farrerol can activate Nrf2 and ameliorate cisplatin-induced acute kidney injury (AKI). Mitophagy reportedly can prevent diabetic nephropathy, cisplatin-induced AKI and other related nephropathy. In this study, we evaluated the correlation between mitophagy and the protective effect of the Nrf2 activator farrerol on cisplatin-induced CKD by using C57BL/6 wild-type and Nrf2 knockout mice. We confirmed that Nrf2 and PINK1/Parkin-mediated mitophagy was significantly increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…A recent study found that NRF2-knockout mice are more sensitive to CP and more likely to suffer severe kidney damage than other mice [26]. Furthermore, based on the close association of oxidative stress and mitochondrial dysfunction, this study hypothesized that the protective effect of liquiritigenin depends on the classic antioxidant signaling-NRF2 pathway.…”
Section: Discussionmentioning
confidence: 88%
“…A recent study found that NRF2-knockout mice are more sensitive to CP and more likely to suffer severe kidney damage than other mice [26]. Furthermore, based on the close association of oxidative stress and mitochondrial dysfunction, this study hypothesized that the protective effect of liquiritigenin depends on the classic antioxidant signaling-NRF2 pathway.…”
Section: Discussionmentioning
confidence: 88%
“…Nrf2 participates in the expression and maturation of various anti-oxidative proteins to maintain the homeostasis of oxidation and reduction ( Ying et al, 2018 ). HO-1 is an essential anti-oxidative factor modulated by Nrf2 ( Ma et al, 2021 ). HO-1 decomposes heme to produce carbon monoxide (CO) that promotes the expression of glutamate-cysteine ligase for GSH transformation ( Consoli et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…NFE2L2 is a momentous involvement in supporting the integrity of mitochondria from structural and functional aspect . It was reported that NFE2L2-prompted transcriptional-level regulation of PINK1 rebounds mitophagy and aberrant mitochondrial activity in kidney diseases. , Therefore, SFN may activate mitophagy through the NFE2L2 pathway to obliterate mitochondria and reduce the release of mitochondrial apoptotic factors, thereby inhibiting apoptosis. On the other hand, SFN may mitigate mitochondria oxidative damage through the NFE2L2 pathway, reducing mitochondrial ROS levels, thereby reducing hypoxia-induced oxidative damage to GCs.…”
Section: Discussionmentioning
confidence: 99%